PENERAPAN METODE ECONOMIC ORDER QUANTITY (EOQ) DALAM MANAJEMEN PERSEDIAN IKAN ASIN TENGGIRI PADA PO. SINAR INDAH DESA PAGATAN BESAR KECAMATAN TAKISUNG - Husni Tambrin; Yulia Hafizah (Al-Ujrah | Jurnal Ekonomi Syariah, 2024)
This research is motivated by the use of the Economic Order Quantity (EOQ) method in controlling inventory with the aim of reducing low inventory costs. By implementing EOQ, companies can avoid stock outs which disrupt the smooth supply process of salted mackerel fish and save on storage costs and ordering costs. This study aims to evaluate stock management of salted mackerel fish in PO. Sinar Indah during 2023 using EOQ. The research method used is field research with data collection techniques through interviews and documentation. Data analysis was carried out using the EOQ method. The research results show that the inventory management approach used by PO. Sinar Indah is still simple and traditional. Their policy on the supply of salted mackerel fish has not been consistent, with ordering frequencies that are not optimal. For example, the most efficient order quantity is 37 quintals per order with a frequency of 9 times a year, in contrast to the previous approach which placed orders 43 times with a smaller quantity each time. Economically, implementing EOQ can reduce total inventory costs from IDR 26,819,600 to IDR 10,403,000. Thus, this research provides an illustration that the application of EOQ can improve the efficiency of PO stock management of salted mackerel fish. Beautiful Rays significantly.